Socio-demographic profile of patients suffering from depressive disorder attending psychiatry outpatient department - Niroula, Riju; Upadhyay, Hari Prasad (Journal of Chitwan Medical College, 2020)
Background: Depression is one of the most common mental disorders responsible for considerable morbidity, disability and decreased quality of life. The socio-demographic factors have consistently been identified as important factors in explaining the variability in depression prevalence rates. This study was aimed to evaluate the relationship between depression and these socio-demographic factors. Methods: A descriptive cross-sectional study was conducted among 110 patients above 18years of age of both sexes who met the criteria for diagnosis of Depressive disorder as per ICD-10 DCR in the Psychiatry Outpatient Department of College of Medical Sciences Teaching Hospital, Bharatpur, Nepal. A self- designed semi- structured proforma was developed to obtain the socio-demographic variables and the data were analyzed. Results: Mean age of the patients was 35.61±10.83 years and 62.7% of the patients were females. Married people (65.5%) tended to develop depression compared to unmarried people (25.5%). Rural residents (67.3%) were more prone to suffer from depression than urban residents (32.7%). Most of the patients were illiterate (54.5%) and unemployed (29.1%). Majority were of Hindu (71.8%) religion, Brahmins (27.3%) caste and from lower socioeconomic status (58.2%). Conclusions: This study shows that socio-demographic factors such as age, gender, marital status, residence, level of education, occupation and socioeconomic status were positively associated with depression. This strong association between depression and socio-demographic status which may have long been overlooked may play an important role to understand and treat the disease.